HUBUNGAN KOMUNIKASI INTERPERSONAL DENGAN KINERJA KARYAWAN HOTEL BUMIMINANG PADANG - Fajri, Syahrul; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This purpose of research is to analyze the relation between interpersonal communication with employees performance at Bumiminang Padang. The type is the correlation. Populations in this study are all employees in hotel operations Bumiminang Padang period December 2015 - April 2016 about 82 employees with a sample of 67 people with taking sample proportionate strafied random sampling. Data collection based to likert scale, while data on employee performance is secondary data obtained from HRD Hotel Bumiminang. The result showed that: 1) Communication interpersonal Hotel Bumiminang categorized as good (57%). 2) Performance of employees at Bumiminang Padang categorized as good (97%). 3) Result correlation Perason Product Moment indicate it’s value 0,457 with significance of 5%. This means that there is a positive connection significant between communication interpersonal with the employees performance.Keywords: interpersonal communication, employee performance